Dapur Kawah Sdn. Bhd / Nur Athira Kamaruddin - Nur Athira, Kamaruddin (2020)
Our company Our company is a manufacturing company what produce food under food and beverages company. The company first build in 2019 by Nur Athira. The company does now have SSM registered and only sells food to friends and neighbour. Management We have ten important person that will run the business. These include one Administrative Manager, one Production Manager, one Marketing Manager, one Finance Manager, one Assistant Manager, two chef and three runners. Our product 1. Maman Leaves Rendang 2. Tapioca Leaves Rendang 3. Pegaga Leaves Rendang The market On 1st September 2016, a research had been made by Statista Research Department about package food sales value in Malaysia in 2010,2015 and prediction for 2020. The packaged food sales value in Malaysia is forecasted to be worth 12 billion U.S. dollars in 2020, an increase from 9 billion dollars in 2015. This statistic clearly shows that packaged food industry in Malaysia had high demand from the consumer and can be expended year by year to satisfy consumer satisfaction. Financial projections Based on the size of our market and our defined market area, our sales projections for the first year are RM26,400. We project a growth rate of 0.4% per year for the first three years. The salary for each of the workers will be RM2,725.00, RM1,635.00, RM1,635.00, RM1,284.00, RM4,360 and RM2,176.00. On start-up we will have ten trained staff to run the business and expect to hire four more this year once financing is secured.